SmuMYB113 is the determinant of fruit color in pepino (Solanum muricatum) - Martinez-Sanchez, Marcela; Hunter, Donald A.; Saei, Ali; Andre, Christelle M.; Varkonyi-Gasic, Erika; Clark, Glen; Barry, Emma; Allan, Andrew C. (Frontiers in Plant Science, 2024)
Pepino (Solanum muricatum) is an herbaceous crop phylogenetically related to tomato and potato.Pepino fruit vary in color, size and shape, and are eaten fresh. In this study, we use pepino as a fruit model to understand the transcriptional regulatory mechanisms controlling fruit quality. To identify the key genes involved in anthocyanin biosynthesis in pepino, two genotypes were studied that contrasted in foliar and fruit pigmentation. Anthocyanin profiles were analysed, as well as the expression of genes that encode enzymes for anthocyanin biosynthesis and transcriptional regulators using both RNA-seq and quantitative PCR. The differential expression of the transcription factor genes R2R3 MYB SmuMYB113 and R3MYB SmuATV suggested their association with purple skin and foliage phenotype. Functional analysis of these genes in both tobacco and pepino showed that SmuMYB113 activates anthocyanins, while SmuATV suppresses anthocyanin accumulation.However, despite elevated expression in all tissues, SmuMYB113 does not significantly elevate flesh pigmentation, suggesting a strong repressive background in fruit flesh tissue. These results will aid understanding of the differential regulation controlling fruit quality aspects between skin and flesh in other fruiting species.